The Wisdom of a Broken Heart: How to Turn the Pain of a Breakup into Healing, Insight, and New Love - Susan Piver (New York Atria Books, 2015)
When a relationship ends, the anguish and disappointment can be devastating. A broken heart is genuinely traumatic. Typical recommendations to keep busy, move on, repair your hidden flaws, and then forget about it may not be helpful. In these pages, Susan Piver reveals that heartbreak actually creates an opportunity for genuine emotional and spiritual transformation, enabling you to emerge on the other side stronger, softer, and capable of loving with renewed confidence. In the years following her own experience, relationship writer Susan Piver searched the world's wisdom traditions and discovered that heartbreak can be an uncompromising teacher of authenticity, power, and even joy. She shares that wisdom here, with instantaneously recognizable anecdotes, insights, on-the-spot practices, exercises, meditations, and down-to-earth advice that make The Wisdom of a Broken Heart a steadying prescription of solace and encouragement, wisdom and humor during the hardest time of your life. Like an infinitely patient, trusted friend, Piver tells you in a thousand different ways the most important thing to remember and the easiest to forget: "You're going to be okay."
Keywords: Love; Interpersonal relations; Nonfiction